Optimization of fermentation conditions for green pigment production from Bacillus cereus M116 (MTCC 5521) and its pharmacological application. (1st January 2014) - Banerjee, D.; Mondal, A.; Gupta, M.; Guha, A. K.; Ray, L.
Abstract: Optimal culture conditions for the production of green pigment was investigated. The optimal culture condition for the production of an extracellular green pigment by growing Bacillus cereus M 1 16 (MTCC 5521) in a complex medium containing (g l −1 ) Peptone‐4·0, Beef Extract‐9·0, NaCl‐7·0, MgSO4 ·7H2 O‐1·0 and KH2 PO4 ‐5·0 was as follows pH‐7·0 at 30°C for 72 h in a 5 l fermenter. Aeration rate and agitator speed had no effect on the pigment production. Thin layer chromatogram of the pigment extracted from the fermented broth with chloroform on silica gel GF254 using ethyl acetate and hexane (1 : 1) as solvent showed three fractions. The major fraction (C3 ) was separated out and identified as 9‐methyl‐1, 4, 5, 8‐tetra‐azaphenanthrene. Acute toxicity test revealed the nontoxic nature upto a dose of 2000 mg kg −1, b.wt., of mice. MTT assay showed the cytotoxic nature in HL60 cells having an IC50 of 2·47 mmol. So, this biopigment may have application in food, textile colorant and pharmaceutical industry. Significance and Impact of the Study: This study demonstrated the optimum production of a biopigment (9‐methyl‐1, 4, 5, 8‐tetra‐azaphenanthrene) by fermentation of a complex medium with Bacillus cereus M 1 16 (MTCC 5521) in submerged fermentation. This is the first investigation of toxicity and cytotoxicity activities of this biopigment. The study showed that the purified pigment had no toxicity to healthy albino mice but a high cytotoxicity activity in HL60 cancer cell line in vitro . The biopigment had further displayed dyeing capability to both solidified agar and cotton cloth. Therefore, it may represent a nontoxic and natural alternative to chemical dyes and pigments.